Pengaruh Penerapan Model Pembelajaran Project Based Learning Dalam Upaya Meningkatkan Hasil Belajar Pada Sma Negeri 3 Maluku Tengah - Acim, Acim; Maysuri, Tama; Sopacua, Jems (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to examine the effect of the application of the Project Based Learning (PBL) learning model on student learning outcomes at SMA Negeri 3 Central Maluku. The method used was quantitative with a pseudo-experimental design, involving two groups of students: an experimental group that applied PBL and a control group that used conventional methods. Data was collected through pre-test and post-test tests to measure changes in student learning outcomes. The results of the analysis showed that the experimental group experienced a significant improvement in learning outcomes compared to the control group. The implementation of PBL not only improves students' academic understanding, but also critical, collaborative, and communicative thinking skills. This study recommends the use of PBL as an effective learning method to improve student learning outcomes in the future.